Experimental and numerical investigations on seismic performance of RC bridge piers considering buckling and low-cycle fatigue of high-strength steel bars. (15th January 2021) - Ding, Yang; Wu, Dianqi; Su, Junsheng; Li, Zhong-Xian; Zong, Liang; Feng, Keyan
Highlights: Compare tensile, buckling and low-cycle fatigue properties of HRB400E and HTRB600 steel. Increase in yield strength and slenderness ratio severely weaken low-cycle fatigue life of steel. FEM successfully predicts steel strain, steel fatigue damage and strength degradation of RC piers. Use of HTRB600 steel in RC piers reduces strain demands of longitudinal bars than HRB400E steel. Reveal influence mechanism of concrete strength and axial load ratio on seismic behavior of RC piers. Abstract: In order to promote the application of high-strength steel bars (HSSB) in reinforced concrete (RC) bridge structures, the mechanical properties of HSSB as well as seismic performance of high-strength RC piers were investigated by experimental study and numerical analysis. First, monotonic and low cycle fatigue tests of HRB400E and HTRB600 steel with different slenderness ratios (L/D) were conducted to comparatively study their mechanical properties. Then, quasi-static cyclic tests of seven rectangular RC piers were conducted to study the effects of concrete cover, longitudinal reinforcement yield strength, concrete strength and axial load ratio on seismic behavior of RC piers. Finally, a fiber-based beam-column element was used to simulate the mechanical behavior of steel material and nonlinear response of RC piers. Material tests indicate that HTRB600 steel has lower uniform and fracture elongations, as well as inferior low-cycle fatigue performance than HRB400E steel. Increase of the slenderness ratio (L/D) severely weakens low-cycle fatigue life of steel bars, and the low-cycle fatigue parameters of steel can be fitted for each slenderness ratio, respectively. Even though HTRB600 steel has relatively lower ductility and inferior low-cycle fatigue performance, the RC piers with HTRB600 steel still have higher or at least comparable deformation capacity than that with HRB400E steel. This results from the reduction of strain demands of longitudinal bars by the utilization of HSSB in RC piers. Removing the concrete cover neighboring the longitudinal bars in the plastic hinge region has trivial impact on bar buckling and ultimate displacement of RC piers, which confirms that the concrete cover has already spalled off prior to the initiation of longitudinal reinforcement buckling. With identical steel strength and tie configuration, the ultimate displacement of RC pier with C80 concrete is significantly lower than that with C40 and C60 concrete, while the latter two have similar deformation capacity. Increase of axial load ratio (from 0.06 to 0.18) obviously reduces ultimate displacement of RC piers, since the concrete in the compression zone endures greater compressive stress under higher axial load and thus compressive failure occurs earlier. The ReinforcingSteel material model in OpenSees is calibrated by experimental data to accurately simulate the buckling and low-cycle fatigue properties of HRB400E and HTRB600 steel. The fiber-based finite element model (FEM) can predict the strain development of longitudinal bars of RC piers under cyclic loading, and the resulting low-cycle fatigue damage of steel material as well as strength degradation of RC piers. Combined with experimental study and FEM, this paper reveals the influence mechanisms of different factors on the seismic performance of RC piers in detail.